Stable Gastric Pentadecapeptide BPC 157 as Therapy After Surgical Detachment of the Quadriceps Muscle from Its Attachments for Muscle-to-Bone Reattachment in Rats - Danijel Matek; Irena Matek; Eva Staresinic; Mladen Japjec; Ivan Bojanic; Alenka Boban Blagaic; Lidija Beketic Oreskovic; Ivana Oreskovic; Tihomil Ziger; Tomislav Novinscak; Ivan Krezic; Sanja Strbe; et al. (Pharmaceutics)
Background: This is a novel rat study using native peptide therapy, focused on reversing quadriceps muscle-to-bone detachment to reattachment and stable gastric pentadecapeptide BPC 157 per-oral therapy for shared muscle healing and function restoration. Methods: Pharmacotherapy recovering various muscle, tendon, ligament, and bone lesions, and severed junctions (i.e., myotendinous junction), per-oral in particular (BPC 157/kg/day 10 µg, 10 ng), provides muscle-to-bone reattachment after quadriceps muscle detachment, both complete (rectus muscle) and partial (vastus muscles). Results: Immediately post-injury, and at 1, 2, 3, 5, 7, 14, 21, 28, 60, and 90 days post-injury, quadriceps muscle-to-bone detachment showed definitive healing failure (impaired walking and permanent knee flexure). Contrarily, macro/microscopic, ultrasonic, magnetic resonance, biomechanical, and functional assessments revealed that BPC 157 therapy recovering effects for all time points were consistent. All parameters of the walking pattern fully improved, and soon after detachment and therapy application, muscle approached the bone, leaving a minimal gap (on ultrasonic assessment), and leg contracture was annihilated. The healing process occurs immediately after detachment from both sides: the muscle and the bone. The reattachment fibers from the ends of the muscle could be traced into the new bone formed at the surface (note, at day 3 post-detachment, increased mesenchymal cells occurred with periosteum reactivation). Consequently, at 3 months, the form was stable, and the balance between the muscle and bone was the following: well-organized bone, newly formed as more cortical bone providing a narrower bone marrow space, and the muscle and mature fibers were oriented parallel to the bone axis and were in close contact with bone. Conclusions: Therefore, to achieve quadriceps muscle-to-bone reattachment, the BPC 157 therapy reversing course acts from the beginning, resolving an otherwise insurmountable deleterious course.